Evaluation of adherence to non-pharmacological treatment for arterial hypertension in elderly patients - Aguiar, João Vitor Fernandes e Barros; Viana, Lucas Gomes Fernandes; Vieira, Lucas Ribeiro; Júnior, Raimundo Roberto Amaral Côrtes; Lima, Rosane Araújo Silva (Brazilian Journal of Implantology and Health Sciences, 2024)
Systemic arterial hypertension (SAH) is a chronic condition prevalent among the elderly, and is an important risk factor for cardiovascular diseases and other serious complications. This study aimed to review the recent literature on the non-pharmacological management of SAH, with an emphasis on adherence to interventions such as lifestyle changes, physical activity, and health education. Through a systematic review, 12 articles published between 2020 and 2024 were included, which addressed fundamental aspects for improving adherence to treatment. The results showed that barriers such as sedentary lifestyle, inadequate eating habits, polypharmacy, and socioeconomic limitations hinder commitment to SAH management. However, strategies such as family support, educational programs, and integration of interprofessional teams have proven effective in overcoming these barriers.